2021
DOI: 10.1364/ol.441365
|View full text |Cite
|
Sign up to set email alerts
|

Optimal generation and isolation of attosecond pulses in an overdriven ionized medium

Abstract: We identify optimal conditions for the generation and isolation of attosecond pulses in an overdriven ionized medium. In a high-pressure and highly ionized gas, the spatiotemporal wavefront rotation of a driving laser can be optimized, leading to complete spatial separation of successive attosecond bursts in the far field. The resulting isolated attosecond pulses (IAPs) are much more divergent such that they are spatially separated from the driving laser in the far field. We show that the time delay of near-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These techniques instead confine the HHG emission to a time window (i.e., a "temporal gate") inside multi-and few-cycle pulses, [111,176,187,[192][193][194][195][196][197][198] guaranteeing an IAP emission. Other approaches have also been reported that exploit the spatio-temporal coupling of HHG pulses [116,199,200] or that conveniently employ the transiently-varying nonlinear effects [115,119,201] acting on the driving pulse. However, incorporating any of these IAPgeneration techniques into a scheme that simultaneously delivers high-flux, high-contrast, and energy-tunable IAPs may be experimentally impractical.…”
Section: Attosecond Pulse Generation Driven By Multi-color and Synthe...mentioning
confidence: 99%
“…These techniques instead confine the HHG emission to a time window (i.e., a "temporal gate") inside multi-and few-cycle pulses, [111,176,187,[192][193][194][195][196][197][198] guaranteeing an IAP emission. Other approaches have also been reported that exploit the spatio-temporal coupling of HHG pulses [116,199,200] or that conveniently employ the transiently-varying nonlinear effects [115,119,201] acting on the driving pulse. However, incorporating any of these IAPgeneration techniques into a scheme that simultaneously delivers high-flux, high-contrast, and energy-tunable IAPs may be experimentally impractical.…”
Section: Attosecond Pulse Generation Driven By Multi-color and Synthe...mentioning
confidence: 99%
“…[41] Therefore, the QRS-based induced dipoles have been widely adopted to simulate the macroscopic HHG without the OAM in our previous studies. [42][43][44] The validity of this approach has been checked against results with TDSE-based induced dipoles. [45] However, it is not clear if the replacement of the TDSE with the QRS in the single-atom response can still be valid when simulating the macroscopic vortex HHG driven by the nonzero OAM beam.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of their better temporal resolution, much effort has been paid to the generation of IAPs. There have been a number of established gating methods to produce IAPs in the extreme ultraviolet (XUV) region with duration ranging from a few hundreds to a few tens attoseconds, including amplitude gating [7], ionization gating [8], polarization gating [9], double-optical gating [10], attosecond lighthouse [11,12], multi-color waveform synthesis [13][14][15], and phase-matching in the overdriven regime [16,17]. Beginning around 2011, with the development of mid-infrared (MIR) laser technology [18], several groups have generated continuum harmonic spectra [19][20][21][22][23] in the soft x-ray (SXR) region and a few have reported the characterization of their temporal behaviors [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%